Translation as “Transcreation” and Other Productive “Betrayals” - Camps, Assumpta (TTR, 2022)
Reconceptualization of the subordinate status of the translated text dates to the Baroque period and, more recently, to the crisis of the concept of authorship in post-structuralist criticism. This has given rise to a notion of translation as manipulation or appropriation that challenges traditional criteria of fidelity to the original text. In a similar vein, the Brazilian school, led by Oswald de Andrade in the first half of the 20th century and the brothers Haroldo and Augusto de Campos in the second, stands out over the past century for its more elaborate and appealing view of translation as manipulation, which is clearly linked, in this case, to the creative process. The Brazilian school is interesting for its resolute commitment to the complete visibility of the translator, arguing for a notion of translation as transcreation and presenting the translator as transfingidor [transpretender]. It is thought-provoking because it reformulates the old debate between cosmopolitanism and nationalism in the Latin American context in terms of transculturation and advocates for decentralizing and destabilizing the universal literary tradition from the periphery. This article provides a brief overview of this fascinating though controversial school, focusing on its theoretical basis as well as on the largely neglected figure of the transfingidor.